(Comparative Study on Food Safety Assurance System in Terms of SP, SNI and foodSafe Model for Small Scale Food Industry in Indonesia) - Sudibyo, Agus; Esti Rahayu, Sri; Maman Rohaman, M; Sutrisniati, Dwi; -, Ressytustra (Warta Industri Hasil Pertanian, 2002)
Comparative study on food safety assurance system in trems of SP, SNI, Foodsafe models and development implementing of foodsafe modelfor small scale food industry in indonesia was conducted to increase the performance of small scale food industry in food safety assurance. the methods used was based on descriptive analysis that had development by Hair et al (1987) that are collecting information and data to identify food safety problems issue on small scale food industry, comparative descriptive analysis of the system, and development implementing of foodsafe model for small scale food industry. The result showed thst the food safety problems in small scale food industry were still complex and need to be improved and empowered. The foodsafe model is appropriated as food safety assurance systems for small scale food industry in Indonesia. The food safety audit resulted that three small scale food industries have met foodsafe requirements.